Epidemiological Characteristics of Male Reproductive Cancers in the Republic of Kazakhstan: Ten-Year Trends - Khussan Talipbayevich Umurzakov; Gulnar Metallovna Shalgumbayeva; Dilyara Radikovna Kaydarova; Yerbol Smail; Askar Ibrayev; Sayan Oralchanovich Sagidullin; Yuliya Mikhailovna Semenova (Tehran University of Medical Sciences, 2022)
Background: Epidemiology of male reproductive cancers (MRC) is relatively well studied in developed world nations, but little is known about Central Asian states. We aimed to analyze the changing trends for incidence, mortality and 5-year survival MRC across provinces of the Republic of Kazakhstan. Methods: This was a retrospective cohort study based on data obtained from the Kazakhstan Cancer Registry, which serves as a nationwide database for all histologically confirmed cancer cases. From this, information on all male patients with prostate (PCa) and testicular cancers (TCa) was retrieved for the period from 2010 to 2019. The statistical analysis of official data on incidence, survival, and mortality rates was performed for both the whole country and its provinces. Results: There was a substantial instability of PCa incidence rates, attributed to the execution of screening program from 2013 to 2017. Still, there was a lack of variations in TCa incidence rates. However, PCa screening program had no influence on reduction of mortality rates, which remained relatively stable. There is much heterogeneity between country's provinces in incidence and mortality rates. TCa patients were younger than PCa patients and had better 5-year survival. Conclusion: As compared with many other countries, Kazakhstani men with PCa and TCa have poorer five-year survival, which requires further investigation. Moreover, a careful analysis of diagnostic and treatment strategies utilized at different hospitals across the country would be highly desirable.